Ultrasonography-guided radiofrequency ablation of vascular malformations—The moving shot technique - Sporns, Peter B.; Psychogios, Marios; Blackham, Kristine; Zech, Christoph; Wildgruber, Moritz; Takes, Martin (Frontiers in Medicine, 2024)
Purpose To describe a novel ultrasound-guided technique for percutaneous radiofrequency ablation of vascular malformations—the “moving shot technique.” Methods Preliminary observational cohort study, conducted from June 1, 2019, to January 31, 2021, including all consecutive patients diagnosed with vascular malformations who were treated with ultrasound-guided radiofrequency ablation using the moving shot technique. Only patients who had undergone at least one unsuccessful previous treatment were included (sclerotherapy with ethanol/aethoxysklerol or embolization/surgery). Results Eight patients with a median age of 22 years (interquartile range, 13–31) were included. Patients had different vascular malformations consisting of 1 arteriovenous malformation, 4 venous malformations, and 1 each a mixed venous-lymphatic malformation, a glomuvenous malformation and a FAVA (fibroadipose vascular anomaly). Malformations were located at the limbs in 5 patients (62.5%), the subcutaneous/intramuscular tissue of the body in 2 patients (25%) and at the chin in 1 patient (12.5%). Clinical symptoms were pain in 8 patients (100%), swelling in 6 patients (75%), and partial immobility in 4 patients (50%). All patients showed an improvement of clinical symptoms after treatment with 7 (87.5%) being completely asymptomatic and 1 (12.5%) showing improvement of immobility and pain. No procedural complications, such as nerve damage or skin burns occurred. Conclusion The moving shot technique using ultrasonography-guided radiofrequency ablation is a promising technique for the interventional treatment of vascular malformations and should be validated in multicenter-approaches.